Restaurant management : customers, operations, and employees - Mill, Robert Christie (Upper Saddle River, NJ : Prentice Hall, 2000)
This book presents three elements: customers, the operation (consisting of food and beverage items as weell as the physical facility), and employees. The operator's task is to manage these elements to produce satisfied customers.
Keywords: Restaurant management; Restaurant management